(4x+6)=(6x-11)

Simple and best practice solution for (4x+6)=(6x-11) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (4x+6)=(6x-11) equation:



(4x+6)=(6x-11)
We move all terms to the left:
(4x+6)-((6x-11))=0
We get rid of parentheses
4x-((6x-11))+6=0
We calculate terms in parentheses: -((6x-11)), so:
(6x-11)
We get rid of parentheses
6x-11
Back to the equation:
-(6x-11)
We get rid of parentheses
4x-6x+11+6=0
We add all the numbers together, and all the variables
-2x+17=0
We move all terms containing x to the left, all other terms to the right
-2x=-17
x=-17/-2
x=8+1/2

See similar equations:

| 17+2e=59 | | -6(x+11)=30+6(x+2) | | 2x+(x+2)=180 | | (6x-15)=(4x+11) | | X-212=x | | 74=4x+1 | | -11x-62=142-5x | | -2-5s=4(4-s) | | (16b-2)-5(3b+3)=-3 | | 1+4x=4(14x+26)-x | | 4x+20=x+(x+4)-2x | | X=3a+7 | | 6m+2(m+7)=m-4 | | 11+15x=4(7x+18)-x | | 0.50(10-y)=7 | | 2(-2)+5y=16 | | -43+3m=-60 | | x^2=X-6=0 | | 2/3x+3/8=3/4 | | G=200x-2x | | 13+5x=4(22x+2)+x | | 8m+3/5=7 | | -2w+7/3=9 | | x^2=8/2 | | d^2+11d+30=(d+5)(d+0) | | 4(x+6)=2(x+24) | | 1/n-3/2n=4 | | w+12=21-w | | 20-4x=7+2.5x | | 4n^2+24n=-36 | | M+(m+3)+2(m+1)=5(2+m) | | 5w+2/7=6 |

Equations solver categories